If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 10 = x + -10 + -4 Reorder the terms: 10 + 2x = x + -10 + -4 Reorder the terms: 10 + 2x = -10 + -4 + x Combine like terms: -10 + -4 = -14 10 + 2x = -14 + x Solving 10 + 2x = -14 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 10 + 2x + -1x = -14 + x + -1x Combine like terms: 2x + -1x = 1x 10 + 1x = -14 + x + -1x Combine like terms: x + -1x = 0 10 + 1x = -14 + 0 10 + 1x = -14 Add '-10' to each side of the equation. 10 + -10 + 1x = -14 + -10 Combine like terms: 10 + -10 = 0 0 + 1x = -14 + -10 1x = -14 + -10 Combine like terms: -14 + -10 = -24 1x = -24 Divide each side by '1'. x = -24 Simplifying x = -24
| 10w+4w=-84 | | 6-7x=7x-9x+1 | | N^14m^16*16n^8= | | 17-2x=14+x | | 6(n+3)=12n-12 | | 6(-2a-3)=-90 | | 6(x+5)+2=8(2x-5)+22 | | -19=5(w-8)-8w | | x^2+2x+76=0 | | y=x^4-24x^2-432 | | -.4t=20 | | x/8+19=18 | | 28=-7(6z-9) | | 7x+3=8(x+9) | | Ay+bx-c=0 | | -15=-7y+2(y+5) | | 1/4(48n+12)=1/6(36+36n) | | -.6+t=-.875 | | -29=x-15 | | 8b+3-10=-2(b-2)+3 | | 9+2x=2x+6 | | 3x+137+2x+28=180 | | -2+5k=15-4k | | 7x+17-6x=-3-10 | | 2x^2-2=-202 | | 2x+8=42 | | (p^5+3p^3-3p-1)(p^5-3p^3-3p+1)=0 | | -8(x-6)+2=90 | | -2x=1-(-1) | | .16t-.8=.2 | | 28=7xn | | 3(-2+3x)=-9x-4 |